Understanding the Challenges in the Design, Installation, and Commissioning of Biocontainment Doors. (June 2015) - Margaritis, Dimitrios; Tyler, Nick
Biocontainment doors are a key part of high-containment shells and an integral part of a complex system. Designing a facility for these doors, as well as their installation and commissioning, is a challenging task. This article reviews biosafety regulations and standards to decipher when and where biocontainment doors are required within a high-containment facility. It then illustrates their required biocontainment and fumigation performance. Construction and architectural considerations sourced from past project experiences are included in detail to inform designers and contractors. Furthermore, specialized areas such as Building Management System (BMS) connectivity and redundancy systems are discussed. Finally, this article includes a section on commissioning and functional testing (FAT) of these doors.